Molecular Characterization of Constipation Disease as Novel Phenotypes in CRISPR-Cas9-Generated Leptin Knockout Mice with Obesity - Ji Eun Kim (International Journal of Molecular Sciences, 2020)
(1) Background: We characterized a novel animal model with obesity-induced constipation because constipation is rarely known in genetically engineered mice (GEM); (2) Methods: The changes in the constipation parameters and mechanisms were analyzed in CRISPR-Cas9-mediated leptin (Lep) knockout (KO) mice from eight to 24 weeks; (3) Results: Significant constipation phenotypes were observed in the Lep KO mice since 16 weeks old. These mice showed a significant decrease in the gastrointestinal motility, mucosal layer thickness and ability for mucin secretion as well as the abnormal ultrastructure of Lieberkühn crypts in the transverse colon. The density or function of the enteric neurons, intestinal Cajal cells (ICC), smooth muscle cells, and the concentration of gastrointestinal (GI) hormones for the GI motility were remarkably changed in Lep KO mice. The downstream signaling pathway of muscarinic acetylcholine receptors (mAChRs) were activated in Lep KO mice, while the expression of adipogenesis-regulating genes were alternatively reduced in the transverse colon of the same mice; (4) Conclusions: These results provide the first strong evidence that Lep KO mice can represent constipation successfully through dysregulation of the GI motility mediated by myenteric neurons, ICC, and smooth muscle cells in the transverse colon during an abnormal function of the lipid metabolism.